Adaptive Managers as Emerging Leaders During the COVID-19 Crisis - Bajaba, Abdulah; Bajaba, Saleh; Algarni, Mohammad; Basahal, Abdulrahman; Basahel, Sarah (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) has taken the world by surprise and has impacted the lives of many, including the business sector and its stakeholders. Although studies investigating the impact of COVID-19 on the organizational structure, job design, and employee well-being have been on the rise, fewer studies examined the role of leadership and what it takes to be an effective leader during such times. This study integrates social cognitive theory and conservation of resources theory to argue for the importance of adaptive personality in the emergence of effective leaders during crisis times, utilizing the crisis of COVID-19 as the context for the study. We argue that managers with an adaptive personality tend to have increased self-efficacy levels to lead during a crisis, resulting in increased motivation to lead during the COVID-19 crisis. Furthermore, managers with increased motivation to lead during the COVID-19 crisis are argued to have enhanced adaptive performance, thereby suggesting a serial mediation model where crisis leader self-efficacy and motivation to lead during the COVID-19 crisis act as explanatory mechanisms of the relationship between the adaptive personality and performance of the manager. In order to test our hypotheses, we collected data from 116 full-time managers in Saudi Arabia during the COVID-19 crisis and used hierarchical linear regression as the method of analysis. The findings support all of the hypotheses. A discussion of the results, contributions, limitations, and future directions is included.